2021
DOI: 10.31018/jans.v13i1.2535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indian cooking practices and cookwares on nutritional security: A review

Abstract: Food provides us nutrients and the energy required for growth, reproduction, and maintenance. Energy is required to perform all voluntary and involuntary activities like digestion, respiration, circulation, carrying out professional, household and recreational activities. Despite having rich food diversity, we are using only a few items as our staple food.  With the adoption of eastern cooking practices and cookwares, risk of both pre-and post-transitional diseases like diabetes, cardiovascular diseases, malnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Germination is an effective and low-cost method that is used to increase the phytase enzyme release to break the phytic acid web and release the minerals present in a plant food web . Tannin and phytate occur naturally in plants and act as antinutrients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Germination is an effective and low-cost method that is used to increase the phytase enzyme release to break the phytic acid web and release the minerals present in a plant food web . Tannin and phytate occur naturally in plants and act as antinutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Tannin forms complexes with proteins, making them less bioavailable, and depletes amino acid depletion . Germination increases the mineral bioavailability of food and in vitro antioxidant activity as a result of the increase in GABA, phenolic, and flavonoid content. , Shunmugapriya et al reported that germination decreases the antinutrient concentration manifold and enhances the protein and starch digestibility. Milk extracted from germinated millets was found to be comparable to commercially available plant-based nondairy milk with respect to appearance and overall acceptability .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations